The role of infant life histories in the construction of identities in death: An incremental isotope study of dietary and physiological status among children afforded differential burial. Issue 3 (21st August 2018) - Craig‐Atkins, Elizabeth; Towers, Jacqueline; Beaumont, Julia
Abstract: Objectives: Isotope ratio analyses of dentine collagen were used to characterize short‐term changes in physiological status (both dietary status and biological stress) across the life course of children afforded special funerary treatment. Materials and methods: Temporal sequences of δ 15 N and δ 13 C isotope profiles for incrementally forming dentine collagen were obtained from deciduous teeth of 86 children from four early‐medieval English cemeteries. Thirty‐one were interred in child‐specific burial clusters, and the remainder alongside adults in other areas of the cemetery. Isotope profiles were categorized into four distinct patterns of dietary and health status between the final prenatal months and death. Results: Isotope profiles from individuals from the burial clusters were significantly less likely to reflect weaning curves, suggesting distinctive breastfeeding and weaning experiences. This relationship was not simply a factor of differential age at death between cohorts. There was no association of burial location neither with stage of weaning at death, nor with isotopic evidence of physiological stress at the end of life. Discussion: This study is the first to identify a relationship between the extent of breastfeeding and the provision of child‐specific funerary rites. Limited breastfeeding may indicate the mother had died during or soon after birth, or that either mother or child was unable to feed due to illness. Children who were not breastfed will have experienced a significantly higher risk of malnutrition, undernutrition and infection. These sickly and perhaps motherless children received care to nourish them during early life, and were similarly provided with special treatment in death.